1998
DOI: 10.1001/archinte.158.5.522
|View full text |Cite
|
Sign up to set email alerts
|

Enterococcus faecium Bacteremia

Abstract: Vancomycin-resistant E faecium bacteremia is a complication of prolonged hospitalization in debilitated patients. Vancomycin resistance has a negative impact on survival in patients with E faecium bacteremia and leads to higher health care costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(24 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…Similar to studies that demonstrated VRE bacteraemia was associated with exposure of patients to VRE contaminated ‘exogenous’ sources [16,31], urinary catheter use was independently associated with the development of VRE bacteraemia. The need for a urinary catheter may also be an indicator of severe underlying illness [16].…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Similar to studies that demonstrated VRE bacteraemia was associated with exposure of patients to VRE contaminated ‘exogenous’ sources [16,31], urinary catheter use was independently associated with the development of VRE bacteraemia. The need for a urinary catheter may also be an indicator of severe underlying illness [16].…”
Section: Discussionsupporting
confidence: 75%
“…In the present study, duration of therapy with specific antibiotics was considered, unlike many earlier studies [12,13,16,17,19-22,24,27,28,30]. Exposure to anti-anaerobic antibiotics has been linked to VRE gastrointestinal tract colonisation [45] and bacteraemia [10,46]; however, the VRE genotype was either vanA VRE [10,46] or not determined [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study has shown the cost of bacteraemia due to GRE to be $27 000 higher than that due to glycopeptide-sensitive enterococci. 110 As with all other infection control interventions, the quality of clinical care must not suffer as a result of the precautions implemented. Due to the uncertainty surrounding the management of GRE, discussion between the infection control team and the clinical staff is essential.…”
Section: Infection Control Measures Principles Of Outbreak Managementmentioning
confidence: 99%
“…Methicillin-resistant Staphylococcus aureus (MRSA), vancomycin-resistant Enterococci (VRE), extended spectrum β-lactamase-producing bacteria (ESBL), multi-drug resistance in Mycobacterium tuberculosis (MDRTB) strains as well as multi-drug resistant Gram-negative bacteria are seen in postoperative surgical patients. Although the data are conflicting, some clues hint at a higher infection-related mortality associated with these resistant organisms [24,25,26,27,28]. …”
Section: Therapy Of Postoperative Bacterial/fungal Infectionsmentioning
confidence: 99%